THE INFLUENCE OF PROCESS PARAMETERS AND APPLICATION OF PROTECTIVE COATING ON MICK-RESTRUCTURE NICKEL SUPER-ALLOY INCONEL-713LC - A. M. Amouei; G. R. Mirhosseini; A. Jafari; V. M. Samoilenko (Научный вестник МГТУ ГА)
The article considers the influence of the parameters of protective coating application process on the structure of the Nickel alloy. Experimental data of the conducted research of the microstructure alloy changes depending on the coating application process are presented. Recommendations on the Nickel alloy structure restoration after coating are proposed.